Damage progression in silicon nitride undergoing non-conforming hybrid cyclic contact. (December 2017) - Raga, Rahul; Khader, Iyas; Chlup, Zdeněk; Kailer, Andreas
Highlights: A systematic study of cyclic contact loading in Si3 N4 was conducted. Lubricated and unlubricated contact were studied under two distinct load levels. Damage initiation and evolution were thoroughly described. Experimentally observed damage was correlated with FEM. Crack initiation location was correlated with contact friction. Abstract: Bearings experience one of the most severe mechanical loading of all machine elements. The contact stresses engendered are highly localised and bound to a very small volume of the material. The aim of this study was to investigate how localised stresses influence the damage mechanism in hybrid contact. Cyclic contact loading of a gas pressure sintered silicon nitride (GPSN) was investigated. Silicon nitride disks and tungsten carbide (WC) indenters were tested under different media, initially at "application relevant" low contact pressures (4–6 GPa) and further on, to accelerate damage, at high contact pressures (10–15 GPa). The low load experiments showed various forms of surface damage with no significant difference between dry and lubricated contact. Whereas, the high load experiments showed different damage behaviour under unlubricated and lubricated conditions. Unlubricated contact resulted in the formation of transfer layers and Hertzian cracks on the silicon nitride surface whereas, damage under lubricated contact was mainly dominated by grain removal and delayed crack formation. Finite element simulations were carried out to study the stress state under different loading conditions. The FEM results indicated that the combination of surface tensile and shear stresses predominantly influence the fatigue damage observed in the experiments rather than fluctuating tensile stresses only.